2021
DOI: 10.1055/s-0040-1721089
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Factors Affecting the Patient-Reported Outcome Measures following Total Knee Replacement: Socioeconomic Factors and Preoperative OKS Have a Clinically Meaningful Effect

Abstract: The Oxford Knee Score (OKS) is a patient-reported outcome questionnaire typically used to assess function and pain in patients undergoing total knee replacement (TKR). However, research is inconclusive as to which preoperative factors are important in explaining variation in outcome following TKR. The operative records of 12,709 patients who underwent primary TKR over a 9-year period were analyzed. The following variables were collected for each patient: age, sex, body mass index (BMI), Index of Multiple Depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Pre-surgical Oxford scores, education level and language spoken at home were also used as covariates in adjusted analyses where patient-reported outcome measures were the outcome of interest. The decision to include these covariates was based on current literature demonstrating worse patient-reported outcomes in populations with lower pre-surgical scores [ 27 , 28 ] and education level [ 29 ]. Language spoken at home was used as a surrogate for cultural background based on research revealing an association between non-Caucasian populations and worse patient-reported outcomes [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pre-surgical Oxford scores, education level and language spoken at home were also used as covariates in adjusted analyses where patient-reported outcome measures were the outcome of interest. The decision to include these covariates was based on current literature demonstrating worse patient-reported outcomes in populations with lower pre-surgical scores [ 27 , 28 ] and education level [ 29 ]. Language spoken at home was used as a surrogate for cultural background based on research revealing an association between non-Caucasian populations and worse patient-reported outcomes [ 30 ].…”
Section: Methodsmentioning
confidence: 99%